Effects of Clostridium butyricum on growth performance, meat quality, and intestinal health of broilers - Li, Zhen; Long, Lingbo; Jin, Xu; Li, Yang; Wu, Qiong; Chen, Xingyong; Geng, Zhaoyu; Zhang, Cheng (Frontiers in Veterinary Science, 2023)
This study investigated the effects of Clostridium butyricum on the growth performance, meat quality and intestinal health of broilers. A total of 800 one-day-old male Arbor Acres broilers were randomly assigned to two groups with 16 replicates of 25 broilers per group and fed with a basal diet (CON) or a basal diet supplemented with 1.5 × 109 cfu/kg C. butyricum and 5 × 108 cfu/kg C. butyricum at 1–21 d and 22–42 d, respectively (CB). The results indicated that C. butyricum significantly increased the final body weight, average daily gain at 1–42 d in the growth performance of broilers (P < 0.05). Moreover, C. butyricum significantly increased a24h* value and pH24h value of breast meat but reduced the drip loss and shear force (P < 0.05). Regarding serum antioxidant indices, C. butyricum significantly increased the total superoxide dismutase (T-SOD) and total antioxidative capacity activities and reduced the malondialdehyde content (P < 0.05). Furthermore, the broilers in the CB demonstrated an increase in jejunal lipase and trypsin activities, villus height (VH) and VH-to-crypt depth ratio at 42 d compared with those in the CON (P < 0.05). C. butyricum also upregulated the intestinal mRNA levels of zonula occludens-1, nuclear factor erythroid 2-related factor 2 (Nrf2), SOD1 and interleukin-10 in the jejunal mucosa (P < 0.05), but it downregulated the mRNA levels of nuclear factor kappa B (NF-κB) and tumor necrosis factor-α (P < 0.05). These results indicate that C. butyricum can improve the growth performance and meat quality of broilers. In particular, C. butyricum can improve the intestinal health of broilers, which is likely to be related to the activation of the Nrf2 signaling pathway and inhibition of the NF-κB signaling pathway.